An evaluation of IEC 61131-3 Ladder diagram and Sequential function chart languages as PLC programming approach for automation system - Jassandi, Muhammad Syahmi (Universiti Teknologi PETRONAS, 2021)
In this modern era, programmable logic controller (PLC) has been widely implemented in automation sector such as industrial controller for production and manufacturing systems that demand high speed, precision and repetitive processes. With IEC61131- 3 standard, programmer can develop the required program, and upload onto the PLC so that the system can work autonomous according to the program. There are five standard languages specified in the IEC61131-3 standard. The programmer can decide to choose any of the five standard languages that suits to their basic knowledge in applying it to PLC or the most suitable language that can be used for realizing the requirements associated to the system that need to be automized. Notably, in this project the focus is on two of the programming languages called as the Sequential function chart (SFC) which offer flexibility and the Ladder diagram (LAD) via movement diagram which is extensively used for programming production and manufacturing systems but has limitations in the branching decision making aspects. The aims of this project have been to find a way of how SFC can be implemented via LAD programming to get the benefit of the SFC approach.